Pharmaceutical systematics: Description and preliminary investigation of an alternative method for structuring drug information - Mary E. Kiersma, Pharm.D., M.S; Aleda M. H. Chenn, Pharm.D., M.S. , GRA; Kristin R. Villa, Pharm.D., GRA; Brian M. Shepler, Pharm.D., Clinical Assistant Professor; Matthew M. Murawski, Corresponding Author, Ph.D., R.Ph., Associate Professor (University of Minnesota Libraries Publishing, 2011)
Objectives: To identify the 30 most common adverse drug events or reactions (ADE/ADRs) within the top 200 medications: (1) by raw incidence, (2) weighted by prescription volume, (3) and weighted by retail dollars. Methods: The Pharmacy Times Top 200 Medications (as ranked by prescription volume) was utilized to identify the top 200 medications in 2008. The ADE/ADRs for each medication were obtained from Facts and Comparisons, Micromedex, and Lexi-Comp and entered into a database. These ADE/ADRs were compiled and summed, identifying the number of times each appeared. These then were ranked to identify the 30 most common ADE/ADRs. The actual prescription volume and total retail dollars for each medication were obtained and listed next to each medication's ADE/ADR. The incidence of each ADE/ADR then was weighted by actual prescription volume and retail dollars to determine the top 30 most common ADE/ADRs.Results: Initial evaluation resulted in 9829 individual ADE/ADRs and summed into 1477 distinct ADE/ADRs, after adjusting for interchangeable terminology. Examples of the 30 most common ADE/ADRs (raw incidence) included: dizziness/vertigo, headache,nausea, vomiting, and diarrhea/loose stools. The list remained the same after weighting by actual prescription volume. After weighting by retail dollars, the order of ADE/ADRs changed slightly.Conclusion: Knowledge of ADE/ADRs is important for pharmacists in all healthcare settings. Consolidating ADE/ADRs for medications may enable pharmacists to recall the most common side effects and aid in earlier identification of ADE/ADRs, which may positively impact patient safety across practice settings.